From suffering towards communal well-being: experiences of a Dalcroze-inspired workshop for a community in crisis - van der Merwe, Liesl; Joubert, Debra; Tempelhoff, Johann Wilhelm (Frontiers in Psychology, 2023)
This qualitative hermeneutic phenomenological study aims to describe the meaning that members of the Parys community ascribed to their experiences of a Dalcroze-inspired workshop. Stakeholders were a number of local residents of Parys, a scenic town situated on the banks of the Vaal River in South Africa’s Free State Province. Local residents were asked to share their water-related experiences at a workshop organized by a North-West University research group. It became clear from their stories that they had experienced severe stressful circumstances. They had suffered stress because of the health risks posed by polluted water and the frequent lapses in the town’s water supply system. Dalcroze-inspired activities were used to facilitate this meeting. Data were collected through focus group interviews, open-ended individual interviews, photos, videos, and observations. All these data were consolidated in one heuristic unit in ATLAS.ti, a computer-assisted qualitative data analysis software program. The codes were organized into categories and themes. Friese’s (2014) notice, collect and think (NCT) method for computer-assisted qualitative data analysis was used. From the data analysis, five themes emerged related to the Dalcroze-inspired activities. It included: joyful experiences, which facilitated social interaction that made it possible for personal relationships to be transformed. Virtues arose from this transformation, and participants’ experience was that the group engagement supported their well-being. We, therefore, argue that the Dalcroze approach can be used in communities in crisis to facilitate conflict resolution and transform relationships.